Towards the adoption of technological innovations: decision processes in transport policy definition - Giovanni Circella (European Regional Science Association (ERSA), 2006)
The widespread of technological innovations is rapidly changing the way modern societies are organized. Such phenomenon highly affects the economy of most developed countries (and, more recently, of developing countries, too), influencing work organization and habits. Besides, technological innovations modify the way in which transport systems are organized, by introducing new transport solutions as well as by upgrading the performances of the existing transport systems, in accordance to a more efficient organization. Several tools have been designed to predict the effects of the adoption of technological innovations in transport. The aim of this paper is to deal with the decision processes involved in the definition of the transport policies for the introduction of such technological solutions. To do this the way in which the new transport solutions affect the local context is analysed. In particular, this work aim to identify the most relevant attributes which influence the decision processes on the adoption of such technological solutions, with reference to their impact on the territory and on the economic activities. To do this, the analysis focuses on the effects involved by the use of wireless technologies and radio frequency identification into seaport infrastructures. Such technologies enable an easier identification of goods in transport terminals; this implies advantages in the organization of the terminal activities, allowing lower time and costs for handling, and at the same time it ensures a greater compliance to security requirements, thus upgrading the level of the performances in these transport systems. On the other hand, the effects of the improvements in transport systems affect the economic context in which transport infrastructures are set. Thus, the adoption of such a technological innovation can represent the chance for local development of the region, due to the better performances of the transport system and to the consequent increased territorial accessibility.
Keywords: 330